Blau syndrome: Lessons learned in a tertiary care centre at Chandigarh, North India - Kumrah, Rajni; Pilania, Rakesh Kumar; Menia, Nitin Kumar; Rawat, Amit; Sharma, Jyoti; Gupta, Anju; Vignesh, Pandiarajan; Jindal, Ankur Kumar; Rikhi, Rashmi; Agarwal, Aniruddha; Gupta, Vishali; Singh, Surjit; et al. (Frontiers in Immunology, 2022)
Objectives: Blau syndrome (BS) is a rare autoinflammatory disease characterized by arthritis, dermatitis, and granulomatous uveitis in early childhood. The study presents the clinical experience of patients with BS at a tertiary care centre in Chandigarh, North India. Methods: Analysis of the clinical profile of patients of BS with NOD2 gene mutations under follow-up was carried out. Results: Diagnosis of BS was genetically confirmed in 11 patients (10 children, one adult; 6 males; 5 females) from 10 families. The median age of onset of symptoms was 12 months (range: 4 months - 4 years), while the age at diagnosis ranged from 2.3 to 26 years. The classical triad of arthritis, dermatitis, and uveitis was present in 6/11 (54.5%) patients. The frequency of arthritis, dermatitis, and uveitis was 100%, 81.8%, and 72.7%, respectively. The median age at diagnosis of ocular symptoms was 4 years (range 2-26 years). Family history was noted in 6 families. Renal involvement was observed in 2 children. All patients in our cohort had the R334W variant in the NOD2 gene. An asymptomatic carrier sibling with R334W mutation was identified in one family. Methotrexate was used as a first-line agent in all children. Adalimumab, which was commenced in 5 patients with uveitis, resulted in significant improvement in 4 patients. The total follow-up duration of the present cohort is 1063.8 patient months. Conclusions: The possibility of BS should always be considered in patients with arthritis and early ocular involvement. Uveitis in patients with BS is severe and usually refractory to conventional Disease-modifying antirheumatic drugs. However, TNF blockers have shown promising results in these patients. Systemic involvement appears to remain a significant cause of morbidity and mortality.